Novel studies in telluride-based phase change materials - Ho, Hui Wen (2015)
Today, telluride-based phase change materials (PCM) are well-suited for data storage applications owing to the large optical and electrical contrasts between phases. Hence, it is important to understand the origin for such fast crystallization as well as explore new materials which better suits application. This thesis first presents a unique property of PCM- redshift in the absorption peak of the crystalline phase relative to its amorphous phase, due to increase in electron delocalization I resonant bonding in the crystalline phase. This phenomenon is explained using the first principle calculations. In addition, the redshift increases with Ge concentration along the GeTe-Sb2 Te3 pseudo-binary line has similar trend as the carrier concentration along the line. These correlations will be addressed in this thesis. Second part of thesis introduces an anomalous PCM, Fe-Te. Its optical and electrical PC properties are anomalous to conventional PCM. This anomalous phenomenon is understood by the derived activation energy, the absorption blueshift and valence band characteristics.